Multiple cullin-associated E3 ligases regulate cyclin D1 protein stability - Lu, Ke; Zhang, Ming; Wei, Guizheng; Xiao, Guozhi; Tong, Liping; Chen, Di (eLife, 2023)
Cyclin D1 is a key regulator of cell cycle progression, which forms a complex with CDK4/6 to regulate G1/S transition during cell cycle progression. Cyclin D1 has been recognized as an oncogene since it was upregulated in several different types of cancers. It is known that the post-translational regulation of cyclin D1 is controlled by ubiquitination/proteasome degradation system in a phosphorylation-dependent manner. Several cullin-associated F-box E3 ligases have been shown to regulate cyclin D1 degradation; however, it is not known if additional cullin-associated E3 ligases participate in the regulation of cyclin D1 protein stability. In this study, we have screened an siRNA library containing siRNAs specific for 154 ligase subunits, including F-box, SOCS, BTB-containing proteins, and DDB proteins. We found that multiple cullin-associated E3 ligases regulate cyclin D1 activity, including Keap1, DDB2, and WSB2. We found that these E3 ligases interact with cyclin D1, regulate cyclin D1 ubiquitination and proteasome degradation in a phosphorylation-dependent manner. These E3 ligases also control cell cycle progression and cell proliferation through regulation of cyclin D1 protein stability. Our study provides novel insights into the regulatory mechanisms of cyclin D1 protein stability and function.
Keywords: cyclin D1; cullin-associated E3 ligase; Keap1; DDB2; WSB2; Rbx1